2018
DOI: 10.33369/joall.v3i2.6821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Indonesian English Textbook for the Ninth Graders of Junior High School “Think Globally Act Locally” From Efl Teachers’ Perspectives

Abstract: The purpose of the study was  to investigate the EFL teachers’ perceptions concerning the textbook of “Think Globally Act Locally” on these criteria: (1) physical and utilitarian attributes, (2) efficient outlay of objectives and supplementary material, (3) learning- teaching content, (4) language skills and aspects. Thirty two EFL teachers of junior high school participated in this study. The instrument consisted of questionnaire and interview. Results indicated that in physical and utilitarian attributes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
(4 reference statements)
1
5
0
Order By: Relevance
“…Mostly, the speaking exercises in the textbook were focused in group tasks that made students quite hard to improve their own speaking skill as they need to pay more attention the group rather than themselves, so as the speaking tasks need to be improved. It was in accordance with research finding by Handayani, Suwarno, and Dharmayana (2018).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Mostly, the speaking exercises in the textbook were focused in group tasks that made students quite hard to improve their own speaking skill as they need to pay more attention the group rather than themselves, so as the speaking tasks need to be improved. It was in accordance with research finding by Handayani, Suwarno, and Dharmayana (2018).…”
Section: Discussionsupporting
confidence: 93%
“…Later on, the research from Basra and Purnawarman (2018) was intended to discover the quality of Think Globally Act Locally e-book. In addition, Handayani, Suwarno, and Dharmayana (2018) Locally Textbook as the primary resource of materials for classroom activity and other teaching media as the complement.…”
Section: Putri Arasuli Sukesimentioning
confidence: 99%
“…Then, Basra and Purnawarman's (2018) study aimed to understand the quality of Think Globally Act Locally e-books. Furthermore, Handayani, Suwarno, and Dharmayana (2018) also evaluated the Think Global Action Locally handbook, but from the perspective of EFL teachers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar studies have been investigated by previous researchers regarding coursebook evaluation in Indonesia. Handayani et al (2018) investigated teachers' perspectives on the Think Globally Act Locally coursebook and found that the coursebook was perceived 'good' for the physical and utilitarian aspects, but the shortcomings were the unnatural coursebook illustrations, lack of teaching aids, boring exercises, lack of vocabulary building, and lack of audio materials for pronunciation practice. Another researcher who investigated a similar topic is Hanifa (2018) who applied document analysis to discover the strengths and weaknesses of two coursebooks used from two different curriculums.…”
Section: Introductionmentioning
confidence: 99%